Kualitas Air Hujan di Desa Sirongo Kecamatan Tidore Utara Kota Tidore Kepulauan - Nur Iswanto Nur Iswanto; Mirna Husen; Agnes Dyah Novitasari Lestari; Chafid Fandel; Dewi Rahyuni Dewi Rahyuni (FMIPA Universitas Papua, 2022)
An analysis of the quality of rainwater has been carried out in rainwater storage tanks in Sirongo Village, North Tidore District, Tidore Islands City. The purpose of this study was to identify the quality of rainwater storage (PAH) based on the drinking water quality requirements according to the Minister of Health of the Republic of Indonesia No. 492/MENKES/PER/IV/2010 and knowing the quantity of water in meeting the drinking water needs of the local community. The results showed that based on the quality standards in the Regulation of the Minister of Health of the Republic of Indonesia No. 492/ Menkes/ Per/ IV/ 2010 concerning requirements for drinking water quality, rainwater quality in Sirongo Village is viewed from the physical parameters (Odor, Taste, Color, Temperature, and turbidity), chemical parameters (Flourida) and biological parameters (total coliform), meet the quality standards, while the chemical parameters (Iron and pH) do not meet the quality standards. Rainwater storage (PAH) in Sirongo village cannot meet the community's water needs because it is influenced by the amount of water used by each family member and the size of the PAH.